2020
DOI: 10.3390/cells9010184
|View full text |Cite
|
Sign up to set email alerts
|

A Review of FoxO1-Regulated Metabolic Diseases and Related Drug Discoveries

Abstract: FoxO1 is a conserved transcription factor involved in energy metabolism. It is tightly regulated by modifications on its mRNA and protein and responds to environmental nutrient signals. FoxO1 controls the transcription of downstream genes mediating metabolic regulation. Dysfunction of FoxO1 pathways results in several metabolic diseases, including diabetes, obesity, non-alcoholic fatty liver disease, and atherosclerosis. Here, we summarize the mechanism of FoxO1 regulation behind these diseases and FoxO1-relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(70 citation statements)
references
References 61 publications
2
68
0
Order By: Relevance
“…Once activated, AKT phosphorylates many downstream targets, including FoxO1 ( 47 ). FoxO1 transcriptionally mediates pathways responsible for many metabolic diseases that are translated by the FoxO1 gene, a member of FoxO genes belonging to the transcription factor (TF) family ( 48 ). The PI3K/AKT pathway has been reported to be important for Treg development both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Once activated, AKT phosphorylates many downstream targets, including FoxO1 ( 47 ). FoxO1 transcriptionally mediates pathways responsible for many metabolic diseases that are translated by the FoxO1 gene, a member of FoxO genes belonging to the transcription factor (TF) family ( 48 ). The PI3K/AKT pathway has been reported to be important for Treg development both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…FOXO1 has been implicated in a variety of cellular processes, such as apoptosis, proliferation, oxidative stress, and inflammation (Kandula et al, 2016). In recent years, FOXO1 has also been associated with tumor development and metabolic diseases, including obesity, diabetes, and atherosclerosis (Peng et al, 2020). The activation of FOXO1 is considered an attractive therapy towards cancers due to its tumor inhibition characteristics (Link, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to TGF‐β1/Smad playing a role in the regulation of fibroblast proliferation and apoptosis, an increasing number of studies showed that the transcription factor forkhead box O1 (FoxO1) was also involved in the regulation of fibroblast proliferation and apoptosis 20 . FoxO1, as a multifunctional transcription factor, is closely related to cell apoptosis, proliferation, oxidative stress, energy metabolism, etc 21,22 Increased FoxO1 activity in diabetic mice 23 plays a key role in wound healing 24 . Therefore, regulating the effects of FoxO1 on cell proliferation and apoptosis is an important way to promote diabetic wound healing 25 …”
Section: Discussionmentioning
confidence: 99%